Atmospheric pressure plasma treatment of polymers : relevance to adhesion - Thomas, Michael, 1970-; Mittal, K. L., 1945- (Hoboken, New Jersey : John Wiley & Sons, 2013)
"The Atmospheric Pressure Plasma (APP) treatment for polymer surface modification has attracted much attention recently, owing to its advantages over other techniques and its ability to improve adhesion without tampering with polymer's bulk properties. Focusing on the utility of APP treatment for enhancing polymer adhesion, this book covers the latest development in this important and enabling technology, providing profound insights from many top researchers on the design and functions of various types of reactors, as well as current and potential applications of APP treatment"--
8.5 ConclusionReferences; Chapter 9: Adhesion Improvement by Nitrogen Functionalization of Polymers Using DBD-based Plasma Sources at Ambient Pressure; 9.1 Introduction; 9.2 Amino Functionalization with Nitrogen-Containing Gases; 9.3 Adhesion Promotion by Amino Functionalization with Nitrogen-Containing Gases; 9.4 Conclusion; Acknowledgements; References; Chapter 10: Adhesion Improvement of Polypropylene through Aerosol Assisted Plasma Deposition at Atmospheric Pressure; 10.1 Introduction; 10.2 Experimental; 10.3 Results and Discussion; 10.4 Conclusions; Acknowledgments; References.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Plastics -- Finishing; Plastics -- Surfaces; Surface preparation; Plasma polymerization; TECHNOLOGY & ENGINEERING / Power Resources / Fossil Fuels; Plasma polymerization; Plastics -- Finishing; Plastics -- Surfaces; Surface preparation; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Electronic books